Ultrasonic impact on bacterial population in sewage sample. (15th May 2008) - Kesari, Kavindra Kumar; Behari, Jitendra
Nine samples of sewage sludge from different paper mills of New Delhi were treated with ultrasonic waves of two different frequencies, viz., 35 kHz and 130 kHz for different time periods (5, 10, 20 and 30 min). Treated sewage sludge was then evaluated with different parameters, viz., Chemical Oxygen Demand(COD), Biochemical Oxygen Demand (BOD), Total Nitrogen, Total Phosphorus, Total Ammonia and Total Viable Count. Bacterial colonies were analysed after staining with Gram stain. Low-frequency ultrasonication was found to be very effective in decreasing the amount of bacterial population in sewage sludge. As the frequency and time period increases, the bacterial populations decrease. Gram-negative bacteria were found to survive in the samples even after treatment.